MOLECULAR THERMODYNAMICS OF MICELLIZATION: MICELLE SIZE DISTRIBUTIONS AND GEOMETRY TRANSITIONS - Santos,M. S. (2016)
Abstract Surfactants are amphiphilic molecules that can spontaneously self-assemble in solution, forming structures known as micelles. Variations in temperature, pH, and electrolyte concentration imply changes in the interactions between surfactants and micelle stability conditions, including micelle size distribution and micelle shape. Here, molecular thermodynamics is used to describe and predict conditions of micelle formation in surfactant solutions by directly calculating the minimum Gibbs free energy of the system, corresponding to the most stable condition of the surfactant solution. In order to find it, the proposed methodology takes into account the micelle size distribution and two possible geometries (spherical and spherocylindrical). We propose a numerical optimization methodology where the minimum free energy can be reached faster and in a more reliable way. The proposed models predict the critical micelle concentration well when compared to experimental data, and also predict the effect of salt on micelle geometry transitions.